Laser Capture Microdissection Coupled Capillary Immunoassay to Study the Expression of PCK-2 on Spatially-Resolved Islets of Rat Langerhans - Pandey, Shashank; Tuma, Zdenek; Smrhova, Tereza; Cedikova, Miroslava; Macanova, Tereza; Chottova Dvorakova, Magdalena (Pharmaceutics, 2021)
The platform for precise proteomic profiling of targeted cell populations from heterogeneous tissue sections is developed. We demonstrate a seamless and systematic integration of LCM with an automated cap-IA for the handling of a very small-sized dissected tissues section from the kidney, liver and pancreatic Langerhans islet of rats. Our analysis reveals that the lowest LCM section area ≥ 0.125 mm2 with 10 µm thickness can be optimized for the detection of proteins through LCM-cap-IA integration. We detect signals ranging from a highly-abundant protein, β-actin, to a low-abundance protein, LC-3AB, using 0.125 mm2 LCM section from rat kidney, but, so far, a relatively large section is required for good quality of results. This integration is applicable for a highly-sensitive and accurate assessment of microdissected tissue sections to decipher hidden proteomic information of pure targeted cells. To validate this integration, PCK2 protein expression is studied within Langerhans islets of normal and diabetic rats. Our results show significant overexpression of PCK2 in Langerhans islets of rats with long-term diabetes.
Keywords: PCK2; multiplexing; capillary Western blotting; laser capture microdissection; Langerhans islets